Computation Ship Resistance Using Computational Fluid Dynamics (CFD) - خلوف علي; محمد نسرين; المحمد علي (Latakia University Journal -Engineering Sciences Series, 2021)
The flow around the DTMB 5415 hull form had been simulated using the finite volume code ANSYS Fluent 2020 R2. Besides, the frictional and the pressure resistance or called as the total resistance for DTMB 5415 hull form, had been calculated at different speed and different draft. The results obtained from the calculation using computational fluid dynamic for model had been compared with it’s of experimental result and Maxsurf result (approximate values). It was found that the values of resistance obtained from the ANSYS Fluent 2020 R2 were almost similar with it’s of experimental data, as the biggest percentage of error was only 3.79 percent for DTMB 5415 model and the error values obtained from the calculation using Maxsurf result (approximate values) were increasing. For future study, the predicted numerical results for the DTMB 5415 model hulls can be improved by using finer mesh elements on the surface of both units and by utilization of more advanced turbulence models such as Detached Eddy Simulation (DES).